Toxic Workplace dan Dampaknya pada Kesehatan Mental hingga Turnover Karyawan - Andini Rohayani; Wilianti Laelatul Fitri; Zulfa Azkia Maharani; Sri Mulyeni (Jurnal bintang manajemen, 2026)
Toxic work environments are becoming an issue that is getting more and more attention in human resource management because of its destructive impact on the psychological well-being of employees and organizational stability. Unhealthy interpersonal relationships, authoritarian leadership, bullying, and recurrent disrespectful behavior create a work atmosphere full of stress and uncertainty. This condition not only triggers work stress, anxiety, and emotional exhaustion, it further exacerbates these challenges, as high work demands and a lack of work-life balance make employees, especially Generation Z, increasingly vulnerable to mental health disorders. This study aims to analyze the influence of toxic work environments on employees' mental health as well as its impact on the intention to quit their jobs. The method used is a literature study with a qualitative approach, analyzing relevant scientific articles. The results of the study showed that a toxic work environment characterized by violence, bullying, tyrannical leadership, unfriendliness, and exclusion had a significant effect on the increase in work stress, psychological pressure, work stress and intention to quit work. Toxic leadership is the main factor in forming an unhealthy work culture. Social support, especially from supervisors, plays a protective role as a protective factor that mediates these negative relationships. Generation Z was found to be more sensitive to injustice and rights violations in the workplace. The study concludes that organizations need to prioritize psychological safety, implement supportive leadership, and provide tangible organizational policies and support to maintain employees' mental health and reduce work stress rates for long-term organizational sustainability.